Sustained antiviral response against in vitro HIV-1 infection in peripheral blood mononuclear cells from people with chronic myeloid leukemia treated with ponatinib - Manzanares, Mario; Ramos-Martín, Fernando; Rodríguez-Mora, Sara; Casado-Fernández, Guiomar; Sánchez-Menéndez, Clara; Simón-Rueda, Alicia; Mateos, Elena; Cervero, Miguel; Spivak, Adam M.; Planelles, Vicente; Torres, Montserrat; García-Gutiérrez, Valentín; et al. (Frontiers in Pharmacology, 2024)
HIV-1 infection cannot be cured due to long-lived viral reservoirs formed by latently infected CD4+ T cells. “Shock and Kill” strategy has been considered to eliminate the viral reservoir and achieve a functional cure but the stimulation of cytotoxic immunity is necessary. Ponatinib is a tyrosine kinase inhibitor (TKI) clinically used against chronic myeloid leukemia (CML) that has demonstrated to be effective against HIV-1 infection in vitro. Several TKIs may induce a potent cytotoxic response against cancer cells that makes possible to discontinue treatment in people with CML who present long-term deep molecular response. In this longitudinal study, we analyzed the capacity of ponatinib to induce an antiviral response against HIV-1 infection in peripheral blood mononuclear cells (PBMCs) obtained from people with CML previously treated with imatinib for a median of 10 years who changed to ponatinib for 12 months to boost the anticancer response before discontinuing any TKI as part of the clinical trial NCT04043676. Participants were followed-up for an additional 12 months in the absence of treatment. PBMCs were obtained at different time points and then infected in vitro with HIV-1. The rate of infection was determined by quantifying the intracellular levels of p24-gag in CD4+ T cells. The levels of p24-gag+ CD4+ T−cells were lower when these cells were obtained during and after treatment with ponatinib in comparison with those obtained during treatment with imatinib. Cytotoxicity of PBMCs against HIV-infected target cells was significantly higher during treatment with ponatinib than during treatment with imatinib, and it was maintained at least 12 months after discontinuation. There was a significant negative correlation between the lower levels of p24-gag+ CD4+ T−cells and the higher cytotoxicity induced by PBMCs when cells were obtained during and after treatment with ponatinib. This cytotoxic immunity was mostly based on higher levels of Natural Killer and Tγδ cells seemingly boosted by ponatinib. In conclusion, transient treatment with immunomodulators like ponatinib along with ART could be explored to boost the antiviral activity of cytotoxic cells and contribute to the elimination of HIV-1 reservoir.